Takayasu arteritis: challenges in diagnosis and management. Issue 7 (25th November 2017) - Kim, Esther S H; Beckman, Joshua
Abstract : Takayasu arteritis (TA) is a rare disease affecting chiefly young women, although it can affect both men and women and persons of many different ethnicities. TA carries a high morbidity rate, but importantly, overall mortality has declined over time such that the 15-year survival rate has increased from 82.9% for patients diagnosed between 1957 and 1975 to 96.5% for those diagnosed from 1976 to 1990. Severity of presenting arterial complications and delay to diagnosis have also decreased over the past decade owing to advances in non-invasive diagnostic imaging and the development of medical therapies. Despite these advances, there still remain significant gaps in the diagnosis and management of these complex patients. These gaps encompass the basic, yet extremely complex, tasks of defining a universally accepted diagnostic criterion, accurate assessment of disease activity and development of clinically meaningful and accurate outcome measures to guide necessary clinical trials for the management of these complex patients.